Essential Role of Complement in Pregnancy: From Implantation to Parturition and Beyond - Girardi, Guillermina; Lingo, Joshua J.; Fleming, Sherry D.; Regal, Jean F. (Frontiers in Immunology, 2020)
The complement cascade was identified over 100 years ago, yet investigation of its role in pregnancy remains an area of intense research. Complement inhibitors at the maternal-fetal interface prevent inappropriate complement activation to protect the fetus. However, this versatile proteolytic cascade also favorably influences numerous stages of pregnancy, including implantation, fetal development, and labor. Inappropriate complement activation in pregnancy can have adverse lifelong sequelae for both mother and child. This review summarizes the current understanding of complement activation during all stages of pregnancy. In addition, consequences of complement dysregulation during adverse pregnancy outcomes from miscarriage, preeclampsia and pre-term birth are examined. Finally, future research directions into complement activation during pregnancy are considered.